Mitigating the effects of climate change in children’s outdoor play environments - Martin Karaba Bäckström; Eva Lundgreen; Björn Slaug (Scandinavian Journal of Occupational Therapy)
Background For many children, public playgrounds represent environments that are playful and important in developing good health. Without efforts to facilitate climate change adaptation of outdoor playgrounds there may be a negative impact on children’s health and well-being.Aim With a special focus on play value, to explore the reasoning and described strategies among professionals responsible for development, planning and solutions concerning outdoor playgrounds in the context of climate change.Materials and methods Eight semi-structured interviews were held with purposefully selected interviewees. Analysis was conducted with manifest content analysis.Results Four themes with supporting categories; 1: a new design paradigm for outdoor play environments, 2: a need for updated regulation- and security guidelines for outdoor play environments, 3: nature-based play environments are more climate change resilient, and 4: maintenance and construction of nature-based outdoor play environments. The findings showed an overall awareness and a will to use innovative and nature-based strategies and planning to deal with climate change implications for outdoor play environments.Conclusions and significance The findings suggest that the strategies employed lean towards implementation of increased ecosystem services and natural elements. Ensuring strengthened resilience against hazardous climate change effects may positively facilitate diverse play activities with high play value.